Genome Evolution in Fungal Plant Pathogens: From Populations to Kingdom-Wide Dynamics - Oggenfuss, Ursula; Feurtey, Alice; Reyes Avila Claudia Sarai; Gluck-thaler Emile; Puccetti, Guido; Glad, Hanna; Abraham, Leen Nanchira; Stalder, Luzia; Moser Tralamazza Sabina; González-sáyer Sandra Milena; Croll, Daniel (Springer International Publishing, 2023)
Plant pathogenic fungi have emerged as major concerns for plant health in agriculture and occupy important niches in natural ecosystems. Pathogen species are often highly diverse and respond rapidly to external factors. Our understanding of how this diverse group of fungi interacts with hosts and the environment has been critically advanced by analyses of fungal genomes. Here, we provide an overview of recent research into surveys of genomic diversity within species and review drivers of diversification including transposable elements. Analyses of epigenetic modifications of the genome have revealed important links to pathogenicity factors and genomic defense mechanisms of the genome. We also review population genomics analyses focused on short-term dynamics in plant pathogens such as recombination, genetic exchange, host adaptation, and the genetic basis of phenotypic traits.